(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with what is word-formation, the different ways in which new words are created in a language and how certain words might have been formed, how many types is the formation of words classified, adding prefixes and suffixes(what are they and which are the most common ones?), as well as the productive and non-productive types of word formation. Word formation studies the derivative structure of existing words and the patterns on which a language builds. What is more, it is a certain principle of classification of lexicon and the main way of enriching the vocabulary.